Shenfu injection promotes self-renewal of intestinal stem cells in sepsis-induced intestinal injury via inducing ATF4 expression - Yunxin Deng; Lingyun Lu; Jinrong Li; Liya Gao; Yihui Wang; Nataša Petrović; Fengyong Yang; You Li; Mei Meng (Frontiers in Pharmacology)
IntroductionShenfu injection (SFI) is widely used in clinical severe conditions including sepsis due to its pharmacological effects of invigorating Qi and reviving Yang for resuscitation. SFI is known to alleviate sepsis-related intestinal injury. However, the underlying mechanism remains exclusive. This study aimed to investigate the regulatory role of SFI in the self-renewal of intestinal stem cells as well as gut microbiota during sepsis.MethodsPlasma of septic patients was collected for detecting intestinal dysfunction markers. Mechanistic investigations were performed using immunofluorescent co-staining, Western Blotting, hematoxylin-eosin(H&E) staining, immunohistochemical (IHC) staining, TUNEL staining, Enzyme-linked immunosorbent assay (ELISA), quantitative reverse transcription-PCR (RT-qPCR) and 16S rRNA gene sequencing.ResultsPlasma levels of D-lactate and intestinal-type fatty acid-binding protein (I-FABP) in septic patients with intestinal dysfunction were significantly reduced following SFI administration. Compared to the control mice, sepsis induced severe mucosal damage in the intestine, including the decrease of the villus length and the number of crypts, which was significantly inhibited by SFI administration. In addition, SFI significantly reduced the levels of pro-inflammatory cytokines Interleukin 1β (IL-1β), Interleukin 6 (IL-6), and tumor necrosis factor-α (TNF-α) in septic mice. Cell proliferation and migration in the intestine were significantly increased in the intestine of septic mice upon SFI treatment. Mechanically, SFI facilitated the expression of activating transcription factor 4 (ATF4) to promote the transcription of SRY-Box Transcription Factor 9 (Sox9), thereby activating the stemness and proliferation of crypt stem cells. Moreover, the gut microbiota composition in septic mice was modulated by SFI administration. In particular, high dose of SFI (HSF) treatment was found to decrease the proportion of harmful bacteria including Proteobacteria and Escherichia-Shigella, while increase the abundance of beneficial bacteria such as Alloprevotella and Butyricimonas in septic mice.DiscussionOur findings revealed that SFI protects against sepsis-induced intestinal injury via promoting the self-renewal of crypt stem cells and regulating the gut microbiota composition, providing strong evidence for the potential of SFI in treating sepsis-related intestinal dysfunction.